Avaliação da efetividade do fechamento dos espaços mesentérico e de Petersen após bypass gástrico em Y de Roux - Geist, Ana Carolina Brochado (2020)
Background: Laparoscopic Roux-en-Y gastric bypass (LRYGB) has been shown to be an effective treatment for morbid obesity. Spite of its effectiveness and relative safety, it is associated with certain long-term complications, the most common is internal hernia (IH). Several modifications in surgical technique have been proposed in an attempt to decrease the incidence of IH, and one of which is the closure of mesenteric defects at the time of primary surgery. The aim of this study is to determine the effectivenes of the closure of mesenteric and Petersen’s spaces in patients after gastric bypass. Methods: Retrospective study from June 2012 to December 2017 in two Centers of Excellence in Bariatric Surgery from Surgery Rewiew Corporation and SBCBM. Patients that were being followed after Roux and Y gastric bypass that needed another laparoscopy due to gallstones had their closure of the mesenteric space reviewed. The presence of failure of the closure was then related with demographics data and excess weight loss information. Results: 210 patients were included, 84% women. The frequency of failure of the closure of mesenteric defects was 4,8% ( CI 95% 2,3-8,6), and only in 1 case the defect was wide open and in 2 cases the defect was larger than 2 cm out of the 10 cases founded. There was no difference between the groups with or without failure in relation to age, BMI, weight loss neither rapid excess weight loss. Conclusion: The closure of the mesenteric and Petersen spaces is an effective maneuver, since during a new laparoscopy the spaces were closed and, in the failed cases, the gaps were so small that do not appear to have a clinical effect.